Efficient Fitting and Rendering of Large Scattered Data Sets Using Subdivision Surfaces - Scheib, Vincent; Haber, Jörg; Lin, Ming C.; Seidel, Hans-Peter (Computer graphics forum, 2002)
We present a method to efficiently construct and render a smooth surface for approximation of large functional scattered data. Using a subdivision surface framework and techniques from terrain rendering, the resulting surface can be explored from any viewpoint while maintaining high surface fairness and interactive frame rates. We show the approximation error to be sufficiently small for several large data sets. Our system allows for adaptive simplification and provides continuous levels of detail, taking into account the local variation and distribution of the data. Categories and Subject Descriptors (according to ACM CCS): G.1.2 [Approximation]: Approximation of surfaces, Least squares approximation, Piecewise polynomial approximation; I.3.3 [Picture/Image Generation]: Display algorithms, Viewing algorithms; I.3.5 [Computational Geometry and Object Modeling]: Surface representation.